PENILAIAN RISIKO KELAUTAN DI KAPAL TUG BOAT DENGAN METODE HIRADC UNTUK AREA OPERASI CONOCOPHILLIPS GRISIK (2015-2018) - Mohamad Rojakoh (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
Tugboats are one type of ship that has a high level of maneuverability. This is very suitable for water activities both at the port and offshore (Kantharia, 2020). This study uses the HIRADC (Hazard Identification Risk Assessment and Determining Control) method that identifies hazards that can occur in routine or non-routine activities on tugs (Petro Suban) in 2015-2018 period , assessing the frequency of occurrence of hazards and their impacts followed by controlling and reduce the value of risk to the point acceptable to the company, the source of research data obtained from risk assessment activities based on the scope of work of the ship such as personal transfer, fuel transfer process and the process of assisting tankers when lifting oil. Research shows that there is the potential for fire and explosion hazards, navigational hazards, collision hazards, dangers of oil spills and people falling into the sea. The potential hazards that have been identified are classified in the high risk classification